Effect of grazing strategies on soil health in pastures, and potential use of spiders as biological indicators : a thesis presented in partial fulfillment of the requirements for a degree of Master of Philosophy in Ecology, Massey University, New Zealand - Pedley, Richard Ian Foster (Massey University, 2023)
Regenerative grazing, involving high-density herds moved frequently to new pastures with extended recovery periods, allows plants more time to produce soil exudates, while trampled residues create a protective mulch layer. This study examined if adopting regenerative grazing practices produces significant changes in soil health indicators compared to non-adopting sites. A grazing score based on herd density, pasture length, and recovery time measured the adoption of regenerative grazing practices. Ground-dwelling spiders were used as a novel indicator of soil health in New Zealand pastoral farms, specifically in relation to regenerative farming practices. Other indicators, including earthworm abundance, soil aggregate sizes, soil carbon levels, pasture diversity, pasture brix levels, soil nutrients, and habitat diversity, were also considered. There were no significant differences in soil health indicators between "regenerative" and "conventional" farms. Secondary analysis exploring the relationship between grazing score and soil health indicators also yielded no significant findings. Pasture slope had an unexpectedly positive effect on some indicators, and habitat diversity had a greater impact on spider abundance than the grazing score. Canonical analysis confirmed the previous findings and identified significant relationships between slope, earthworm abundance, and soil sulphur. In conclusion, adopting regenerative grazing practices did not yield significant changes in soil health indicators compared to non-adopting sites. Spiders, which were primarily introduced species, were not effective indicators, due to their low abundance in pasture habitats. The study recommends measuring multiple soil biological health indicators collectively to comprehensively assess agricultural practices' impact on soil health.
Keywords: 410601 Land capability and soil productivity